Pembelajaran Cooperative Learning Berbantuan Media Scrabble dalam Pembelajaran IPS pada Siswa SMP - Lies Sunarmintyastuti; Hugo Aries Suprapto; Lusiana Wulansari; Loecita Sandiar; Lidya Natalia Sartono (Peneliti.net, 2020)
Learning in schools requires continuous innovation and development. This needs to be done, because students must get quality and creative learning. One method that emphasizes cooperative learning is cooperative learning assisted by scrabble media. The purpose of this study was to describe scrabble-assisted cooperative learning in social studies for grade IX students. The method used is a classroom action research method. The results showed that the use of scrabbled-assisted cooperative learning methods could assist classroom learning in social studies subjects. The increase in value from pre-cycle to second cycle is 12 points. Learning is more dynamic and runs actively. The students are active and always looking for good answers.